Auxin-Mediated Regulation of Dorsal Vascular Cell Development May Be Responsible for Sucrose Phloem Unloading in Large Panicle Rice - Deng, Yao; Yu, Yongchao; Hu, Yuxiang; Ma, Li; Lin, Yan; Wu, Yue; Wang, Zhen; Wang, Ziteng; Bai, Jiaqi; Ding, Yanfeng; Chen, Lin (Frontiers in Plant Science, 2021)
Large panicle rice cultivars often fail to fulfil their high-yield potential due to the poor grain filling of inferior spikelets (IS), which appears as initially stagnant development and a low final seed weight. Understanding the mechanism of the initial stagnancy is important to improve IS grain filling. In this study, superior spikelets (SS) were removed from two homozygous japonica rice varieties (W1844 and CJ03) with the same sink capacity in an attempt to force photosynthate transport to the IS. The results showed that SS removal increased the grain weight, sucrose content, starch accumulation and endogenous IAA levels of IS during the initial grain-filling stage. SS removal also improved the patterns of vascular cells in the dorsal pericarp and the expression levels of genes involved in sucrose transport (OsSUTs and OsSWEETs) and IAA metabolism (OsYUCs and OsPINs). Exogenous IAA application advanced the initiation of grain filling by increasing the sucrose content and the gene expression levels of sucrose transporters. These results indicate that auxin may act as a signal substance and play a vital role in initial grain filling by regulating dorsal vascular cell development and sucrose phloem unloading into caryopsis.